2017
DOI: 10.3171/2017.3.peds1734
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric superior semicircular canal dehiscence: illustrative case and systematic review

Abstract: OBJECTIVEThe purpose of this study is to present an illustrative case of pediatric superior semicircular canal dehiscence (SSCD) and to systematically review the current published literature in the pediatric population.METHODSAn electronic search of the Scopus, Web of Science, PsycINFO, Cochrane, and Embase databases was performed by 2 independent authors through January 2017. Search term combinations incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
(56 reference statements)
1
19
0
Order By: Relevance
“…As discussed earlier, a cochlear hearing loss can be a feature of semicircular dehiscences in children and this hearing loss can serve as a phenotype for the condition. The extensive study by Lagman et al (37) analyzing data in existing literature pertaining to SSCD in children concluded that hearing loss was the commonest indication for performing a high resolution CT scan that showed SSCD; however, it must be noted that about 25% children in this analysis had other causes explaining the hearing loss. The current series is the first to exclude this comorbidity group by performing extensive investigation for hearing loss and also employed other features for example third window symptoms and disequilibrium and vestibular function tests as indicators for further imaging.…”
Section: Discussionmentioning
confidence: 72%
“…As discussed earlier, a cochlear hearing loss can be a feature of semicircular dehiscences in children and this hearing loss can serve as a phenotype for the condition. The extensive study by Lagman et al (37) analyzing data in existing literature pertaining to SSCD in children concluded that hearing loss was the commonest indication for performing a high resolution CT scan that showed SSCD; however, it must be noted that about 25% children in this analysis had other causes explaining the hearing loss. The current series is the first to exclude this comorbidity group by performing extensive investigation for hearing loss and also employed other features for example third window symptoms and disequilibrium and vestibular function tests as indicators for further imaging.…”
Section: Discussionmentioning
confidence: 72%
“…Younger adults and those over age 65 tend to present with similar symptoms, as do men and women [40]. Cases of SCDS in children have been identified [20,29]. Children tend to report more auditory symptoms and may report hyperacusis or generalized dizziness [29].…”
Section: Demographics Of Superior Semicircular Canal Dehiscence Syndromementioning
confidence: 99%
“…Cases of SCDS in children have been identified [20,29]. Children tend to report more auditory symptoms and may report hyperacusis or generalized dizziness [29]. Differences in presenting symptoms between children and adults may be attributed to younger children having difficulty explaining their symptoms to adults.…”
Section: Demographics Of Superior Semicircular Canal Dehiscence Syndromementioning
confidence: 99%
“…The children with mixed losses above 30 dBHL in the series returned absent TEOAEs. Sensorineural hearing loss has been reported in pediatric SCDS ( 5 , 66 68 ). There was 1 child with normal hearing that has also been reported in third window disorders ( 5 , 68 ).…”
Section: Discussionmentioning
confidence: 99%